Aligned nanotriangles of tantalum doped tungsten oxide for improved photoelectrochemical water splitting - Kalanur, Shankara S.; Seo, Hyungtak (Journal of Alloys and Compounds, 2019)
Tuning the optical and electrical properties of WO3 via doping is an efficient strategy to improve its photoelectrochemical (PEC) water splitting activity. In this article, a simple hydrothermal method is utilized to fabricate Ta-doped WO3 nanotriangle thin films for the PEC water splitting applications. The doping of Ta converts the nanorod structure of undoped WO3 into nanotriangle morphology. During the synthesis, the Ta is doped to orthorhombic WO3·0.33H2O and converted to hexagonal phase via annealing. The presence of Ta in the WO3 lattice obstruct the reconstructive transformation of orthorhombic to monoclinic phase producing Ta-doped WO3 with hexagonal phase. The optimum amount of Ta (1.88 at%) causes the reduction in the band gap and increase the oxygen vacancies and carrier density in WO3 lattice. Compared to undoped WO3, Ta-doped WO3 nanotriangles exhibit higher photocurrent and incident photon to current efficiency values. Finally, the possible band structure is proposed for the Ta-doped WO3 based on the spectroscopic and electrochemical data. The results of the present work suggest that Ta doping alters the band edge positions of WO3 and has the potential to improve the PEC water splitting activity of WO3.
Keywords: Band edge position; Hexagonal; Incident photon-to-current efficiencies; Optical and electrical properties; Photoelectrochemical water splitting; Photoelectrochemicals; Reconstructive transformation; Tungsten oxide; Band edge position; Doping; Hexagonal; Photoelectrochemical water splitting; Tantalum; Tungsten oxide